Electrode plate, preparation method of electrode plate, all-solid-state battery and electric device
By setting a solid electrolyte content gradient in the electrode sheet of an all-solid state battery and adding solvent binder, the high resistance problem of the electrode material and electrolyte interface in the battery is solved, and the cycling performance and first-term effect of the battery are significantly improved.
Patent Information
- Application Number
- CN202411825775.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The interface between the electrode material and the electrolyte in an all-solid state battery is a solid interface, with a large interface resistance, which is not conducive to lithium ions or electron transmission, resulting in poor circulation performance.
The preparation method of electrode sheet is adopted, which includes setting a solid electrolyte content gradient in the electrode material layer and adding a small amount of solvent binder during the dry electrode preparation process to reduce the breakage of the active substance during the rolling process and improve the electron transport efficiency.
By optimizing the distribution of solid electrolytes and reducing the breakage of electrode materials, the transmission channels of lithium ions and electrons are improved, and the circulation performance and first-time effect of all-solid-state batteries are significantly improved.
Smart Images

Figure CN119650584A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to an electrode plate, a method for preparing the electrode plate, an all-solid-state battery and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have attracted much attention in the fields of electric vehicles and energy storage due to their excellent performance and wide range of application scenarios. At present, lithium-ion batteries are mostly prepared by wet process, which is simple and mature in technology and is the choice of most battery manufacturers. However, the capacity density of wet-process batteries has reached a bottleneck, and their performance in safety tests such as hot boxes and penetration tests is average. At the same time, as consumers' requirements for battery capacity and safety performance increase, all-solid-state batteries with higher energy density and safety performance have received a lot of attention.
[0003] All-solid-state batteries have a more stable and wider electrochemical window, which can be compatible with positive and negative electrodes of specific capacity, and significantly improve the energy density of the battery. At the same time, solid electrolytes have high mechanical strength and are non-flammable, which can greatly reduce the risk of thermal runaway of the battery. However, since the interface between the electrode material and the electrolyte in the solid-state battery is a solid-solid interface, the interface resistance is large, which is not conducive to the transmission of lithium ions or electrons, resulting in poor cycle performance. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, embodiments of the present invention provide an electrode plate, a method for preparing the electrode plate, an all-solid-state battery, and an electrical device.
[0006] In a first aspect, the present invention provides an electrode plate, comprising:
[0007] current collector;
[0008] An electrode material layer is rolled and arranged on the surface of the current collector, and the electrode material layer includes a first electrode material layer and a second electrode material layer which are rolled and arranged on the surface of the current collector in sequence, and the mass proportion of the solid electrolyte in the first electrode material layer is 3% to 5% lower than the mass proportion of the solid electrolyte in the second electrode material layer.
[0009] Solid electrolytes include LLZO, LATP, LLTO, etc. There is ion transmission and electron transmission in solid-state batteries. From the diaphragm to the current collector, the number of lithium ions continues to decrease, while the number of electrons continues to increase. The solid electrolyte mainly plays the role of ion transmission, and if there are too many solid electrolytes on the current collector side, it is not conducive to electron transmission, affecting the capacity and cycle performance. In the present invention, the mass proportion of the solid electrolyte in the first electrode material layer is less than the mass proportion of the solid electrolyte in the second electrode material layer to improve the cycle performance of the solid-state battery.
[0010] Furthermore, the electrode plate is a positive electrode plate or a negative electrode plate.
[0011] Furthermore, the electrode material layer is obtained by uniformly mixing active material, conductive agent and solid electrolyte, adding binder and solvent binder, stirring at high speed to obtain powder, and calendering the powder.
[0012] If the active material powder is broken during the rolling process, the specific surface area will be significantly increased, and the number of solid-solid interfaces will also increase significantly, which will lead to the interruption of the contact sites between the powders, resulting in a decrease in the capacity of the battery, an increase in the internal resistance, and a negative impact on the cycle performance. In the present invention, by adding a solvent binder, the lubrication effect of the solvent binder is utilized to reduce the breakage of the active material during the rolling process, thereby improving the cycle performance of the solid-state battery.
[0013] Furthermore, the added amount of the solvent binder is 1% to 5% of the added amount of the active substance.
[0014] The amount of solvent binder added is 1%, 2%, 3%, 4%, 5% of the amount of active material added, or a value within the range of any two values. The appropriate amount of solvent binder added allows the powder to be fully lubricated during the rolling process; when the amount of solvent binder added is too much, the solvent binder is difficult to completely volatilize during the hot pressing process, resulting in some solvent binder residues, affecting battery performance; when the amount of solvent binder added is too little, the powder is not fully lubricated, and it is difficult to protect the solvent binder from breaking.
[0015] Furthermore, the boiling point of the solvent binder is below 100° C. When the boiling point is below 100° C., the solvent binder is volatilized during the hot pressing process and does not affect subsequent processes.
[0016] The solvent binder is an organic solvent with low polarity and low boiling point. It plays the role of wetting the powder particles, reducing the rigid contact between particles and reducing the breakage of active substances during rolling. At the same time, during the hot pressing process, the solvent binder is volatilized and removed, which has no effect on the subsequent process. Polarity refers to the uneven distribution of positive and negative charges in molecules, which causes the molecules to have a positive and negative charge orientation in the electric field. Solvent binders with excessive polarity have poor stability and will produce side reactions.
[0017] Furthermore, the solvent binder includes one of cyclohexane, cyclopentane, n-pentane, ethane, isooctane, trimethylpentane, diethyl ether, propyl ether, petroleum ether and benzene.
[0018] In a second aspect, the present invention provides a method for preparing the electrode sheet according to the first aspect, such as Figure 1 As shown, the following steps are included:
[0019] (1) mixing a first active material, a first conductive agent, and a first solid electrolyte uniformly, then adding a first binder and a first solvent binder, and then mixing uniformly and stirring at a high speed to fiberize the first solvent binder to obtain a first powder;
[0020] (2) after the second active material, the second conductive agent and the second solid electrolyte are mixed evenly, a second binder and a second solvent binder are added, and after the mixture is evenly mixed, the mixture is stirred at a high speed to fiberize the second solvent binder to obtain a second powder;
[0021] (3) respectively rolling the first powder and the second powder at room temperature to obtain a first electrode material layer and a second electrode material layer;
[0022] (4) After rolling the first electrode material layer onto the current collector at room temperature, rolling the second electrode material layer onto the first material layer at 100-160° C. to obtain an electrode sheet.
[0023] Furthermore, the thickness of the electrode plate is 40-70 μm.
[0024] In a third aspect, the present invention proposes an all-solid-state battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet are the electrode sheets proposed in the first aspect or the electrode sheets prepared by the method proposed in the second aspect.
[0025] In a fourth aspect, the present invention proposes an electrical device comprising the all-solid-state battery proposed in the third aspect.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] In the dry electrode preparation process of the present invention, a small amount of solvent binder is added to wet the powder particles, reduce the rigid contact between the particles, and reduce the breakage of the active material during the rolling process. During the hot pressing process, the solvent binder is volatilized and removed without affecting the subsequent process. A solid electrolyte content gradient design is adopted to optimize the transmission channel of lithium ions and electrons and improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0029] Figure 1 The present invention is a flow chart of the method for preparing the electrode plate. DETAILED DESCRIPTION
[0030] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0031] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0032] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0033] Example 1
[0034] Positive electrode preparation:
[0035] 80g LiNi 0.6 Co 0.2 Mn 0.2 O2, 2g SP, 3g VGCF, and 13g LATP were stirred at 300rpm for 10min to be evenly mixed, and then 2g PTFE and 2g cyclohexane were added, first stirred at 300rpm for 12min to be evenly mixed, and then stirred at 1500rpm for 15min to fiberize the PTFE to obtain the first positive electrode powder.
[0036] 80g LiNi 0.6 Co 0.2 Mn 0.2O2, 0.8g SP, 1.2g VGCF, and 17g LATP were stirred at 300rpm for 10min to be evenly mixed, and then 1g PTFE and 2g cyclohexane were added, first stirred at 300rpm for 12min to be evenly mixed, and then stirred at 1500rpm to fiberize the PTFE to obtain the second positive electrode powder.
[0037] The first positive electrode powder is rolled at room temperature to obtain a first positive electrode material layer with a thickness of 40 μm, and the second positive electrode powder is rolled at warm pressure to obtain a second positive electrode material layer with a thickness of 40 μm. The first positive electrode material layer and the aluminum foil are first rolled together by a double roller machine, and then the second positive electrode material layer is rolled together with the aluminum foil pressed with the first positive electrode material layer by a double roller machine at 100°C to obtain a positive electrode sheet.
[0038] A solid electrolyte membrane composed of 98% LATP and 2% PTFE is rolled on both sides of the positive electrode sheet with a thickness of 8 μm.
[0039] Negative electrode sheet preparation:
[0040] 81 g of graphite, 4.5 g of SP, and 13.5 g of LLZO were stirred at 150 rpm for 10 min to mix evenly, and then 1 g of PTFE and 2 g of cyclohexane were added, first stirred at 150 rpm for 10 min to mix evenly, and then stirred at 1000 rpm for 15 min to fiberize the PTFE to obtain the first negative electrode powder.
[0041] 81 g of graphite, 0.5 g of SP, and 17.5 g of LLZO were stirred at 150 rpm for 10 min to mix evenly, and then 1 g of PTFE and 2 g of cyclohexane were added, first stirred at 150 rpm for 14 min to mix evenly, and then stirred at 1000 rpm for 15 min to fiberize the PTFE to obtain the second negative electrode powder.
[0042] The first negative electrode powder is rolled at room temperature to obtain a first negative electrode material layer with a thickness of 50 μm, and the second negative electrode powder is rolled at warm pressure to obtain a second negative electrode material layer with a thickness of 50 μm. The first negative electrode material layer and the aluminum foil are first rolled together by a double roller machine, and then the second negative electrode material layer is rolled together with the copper foil pressed with the first negative electrode material layer by a double roller machine at 120°C to obtain a negative electrode sheet.
[0043] A solid electrolyte membrane composed of 98% LLZO and 2% PTFE is rolled on both sides of the negative electrode sheet with a thickness of 8μm.
[0044] Battery Assembly:
[0045] The positive electrode sheet, solid electrolyte membrane, and negative electrode sheet are stacked in sequence, and the electrode assembly is placed in an outer packaging aluminum-plastic film. After vacuum packaging, standing, and formation processes, a 2.4Ah all-solid-state battery is obtained.
[0046] Example 2
[0047] The difference from Example 1 is that the content of LATP in the second positive electrode powder is 18.2 g; the content of LLZO in the second negative electrode powder is 18.7 g; and the solvent binder is 2 g of diethyl ether.
[0048] Example 3
[0049] The difference from Example 1 is that the LATP in the second positive electrode powder is 15.8 g; the LLZO in the second negative electrode powder is 16.3 g; and the solvent binder is 2 g of n-pentane.
[0050] Example 4
[0051] The difference from Example 1 is that the amount of cyclohexane added to the first positive electrode powder, the second positive electrode powder, the first negative electrode powder, and the second negative electrode powder is 4 g.
[0052] Example 5
[0053] The difference from Example 1 is that the amount of cyclohexane added to the first positive electrode powder, the second positive electrode powder, the first negative electrode powder, and the second negative electrode powder is all 1 g.
[0054] Comparative Example 1
[0055] The difference from Example 1 is that cyclohexane is not added to the first positive electrode powder, the second positive electrode powder, the first negative electrode powder, and the second negative electrode powder.
[0056] Comparative Example 2
[0057] Positive electrode preparation:
[0058] 80g LiNi 0.6 Co 0.2 Mn 0.2 O2, 0.8g SP, 1.2g VGCF, and 17g LATP were stirred at 300rpm for 10min to be evenly mixed, and then 2g PTFE and 2g cyclohexane were added, first stirred at 300rpm for 12min to be evenly mixed, and then stirred at 1500rpm to fiberize the PTFE to obtain the positive electrode powder.
[0059] The positive electrode powder was rolled at room temperature to obtain a positive electrode material layer with a thickness of 40 μm, and the positive electrode material layer and the aluminum foil were rolled together at 100° C. using a double-roller machine.
[0060] A solid electrolyte membrane composed of 98% LATP and 2% PTFE is rolled on both sides of the positive electrode sheet with a thickness of 8 μm.
[0061] Negative electrode sheet preparation:
[0062] 81 g of graphite, 0.5 g of SP, and 17.5 g of LLZO were stirred at 150 rpm for 10 min to mix evenly, and then 1 g of PTFE and 2 g of cyclohexane were added, first stirred at 150 rpm for 14 min to mix evenly, and then stirred at 1000 rpm for 15 min to fiberize the PTFE to obtain anode powder.
[0063] The negative electrode powder was rolled at room temperature to obtain a negative electrode material layer with a thickness of 50 μm, and the negative electrode material layer and the copper foil were rolled together at 120° C. using a double-roller machine.
[0064] A solid electrolyte membrane composed of 98% LLZO and 2% PTFE is rolled on both sides of the negative electrode sheet with a thickness of 8μm.
[0065] Battery Assembly:
[0066] The process is the same as in Example 1.
[0067] Comparative Example 3
[0068] Positive electrode preparation:
[0069] 80g LiNi 0.6 Co 0.2 Mn 0.2 O2, 0.8g SP, 1.2g VGCF, and 17g LATP were stirred at a low speed of 300rpm for 10min to be evenly mixed, and then 2g PTFE was added, first stirred at 300rpm for 12min to be evenly mixed, and then stirred at a high speed of 1500rpm to fiberize the PTFE to obtain a positive electrode powder.
[0070] The positive electrode powder is rolled at room temperature to obtain a positive electrode material layer with a thickness of 40 μm, and the positive electrode material layer and the aluminum foil are rolled together at room temperature by a double-roller machine.
[0071] A solid electrolyte membrane composed of 98% LATP and 2% PTFE is rolled on both sides of the positive electrode sheet with a thickness of 8 μm.
[0072] Negative electrode sheet preparation:
[0073] 81 g of graphite, 0.5 g of SP, and 17.5 g of LLZO were stirred at 150 rpm for 10 min to be uniformly mixed, and then 1 g of PTFE was added and stirred at 150 rpm for 14 min to be uniformly mixed, and then stirred at 1000 rpm for 15 min to fiberize the PTFE to obtain a negative electrode powder.
[0074] The negative electrode powder is rolled at room temperature to obtain a negative electrode material layer with a thickness of 50 μm, and the negative electrode material layer and the copper foil are rolled together at room temperature by a double-roller machine.
[0075] A solid electrolyte membrane composed of 98% LLZO and 2% PTFE is rolled on both sides of the negative electrode sheet with a thickness of 8μm.
[0076] Battery Assembly:
[0077] The process is the same as in Example 1.
[0078] Comparative Example 4
[0079] The difference from Example 1 is that the amount of cyclohexane added to the first positive electrode powder, the second positive electrode powder, the first negative electrode powder, and the second negative electrode powder is 6 g.
[0080] Comparative Example 5
[0081] The difference from Example 1 is that the LATP in the second positive electrode powder is 13.5 g; the LLZO in the second negative electrode powder is 14 g; and the solvent binder is 2 g of diethyl ether.
[0082] Comparative Example 6
[0083] The difference from Example 1 is that the LATP in the second positive electrode powder is 20.75 g; the LLZO in the second negative electrode powder is 21.3 g; and the solvent binder is 2 g of n-pentane.
[0084] Test example
[0085] The all-solid-state batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested for first efficiency, cycle life, and thermal runaway temperature. The test results are shown in Table 1 below.
[0086] The test method is as follows:
[0087] First efficiency: Test the percentage of 0.33C discharge capacity divided by 0.1C first week charge capacity;
[0088] Thermal runaway temperature: Heat the battery cell to 180°C and keep it warm for 30 minutes; when thermal runaway does not occur, further increase the temperature by 5°C and keep it warm for 30 minutes; repeat this step, increasing the temperature by 5°C and keeping it warm for 30 minutes each time until thermal runaway occurs, and obtain the thermal runaway temperature value.
[0089] Cycle life: The number of cycles of 0.5C charge / 0.5C discharge until the capacity retention rate drops to 80%.
[0090] Table 1:
[0091] Grouping First effect Cycle life Thermal runaway temperature Example 1 85.7% 756 220 Example 2 83.2% 707 225 Example 3 80.1% 683 215 Example 4 84.4% 729 220 Example 5 84.1% 714 220 Comparative Example 1 75.4% 608 215 Comparative Example 2 79.2% 646 215 Comparative Example 3 71.9% 550 210 Comparative Example 4 80.1% 670 215 Comparative Example 5 79.8% 684 215 Comparative Example 6 79.4% 661 225
[0092] According to Table 1, we can see that:
[0093] The first effect, cycle life and thermal runaway temperature of the batteries of Examples 1 to 5 are generally better than those of Comparative Examples 1 to 6;
[0094] According to Example 1 and Comparative Examples 1 and 4, it can be seen that excessive addition of solvent binder or no addition is not conducive to improving the performance of solid-state batteries.
[0095] According to Example 1 and Comparative Examples 2, 5 and 6, it can be seen that when the solid electrolyte content is not designed to be gradient distributed or the gradient is designed to be too large or too small, the cycle and first-efficiency performance of the all-solid-state battery decreases. It can be seen that the gradient distribution of the solid electrolyte content improves the cycle performance and first efficiency of the all-solid-state battery, and a gradient that is too large or too small is not conducive to improving the performance of the all-solid-state battery.
[0096] According to Example 1 and Comparative Example 3, when the solid electrolyte content is not designed to be gradient distributed and no solvent binder is added, the cycle and first efficiency performance of the all-solid-state battery decrease. It can be seen that the gradient distribution of the solid electrolyte content and the addition of a solvent binder improve the cycle performance and first efficiency of the all-solid-state battery.
[0097] The present invention adds a solvent binder to the binder to reduce the breakage of the active material powder during the rolling process, adjust the solid electrolyte content of the upper and lower layers of the pole piece, and improve the transmission path, thereby improving the cycle performance and the first effect of the all-solid electrolyte.
[0098] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0099] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0100] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. An electrode plate, characterized in that: include: current collector; An electrode material layer is rolled and arranged on the surface of the current collector, and the electrode material layer includes a first electrode material layer and a second electrode material layer which are rolled and arranged on the surface of the current collector in sequence, and the mass proportion of the solid electrolyte in the first electrode material layer is 3% to 5% lower than the mass proportion of the solid electrolyte in the second electrode material layer.
2. The electrode plate according to claim 1, characterized in that: The electrode plate is a positive electrode plate or a negative electrode plate.
3. The electrode plate according to claim 1, characterized in that: The electrode material layer is obtained by uniformly mixing active material, conductive agent and solid electrolyte, adding binder and solvent binder, stirring at high speed to obtain powder, and calendering the powder.
4. The electrode plate according to claim 4, characterized in that: The added amount of the solvent binder is 1% to 5% of the added amount of the active material.
5. The electrode plate according to claim 4, characterized in that: The boiling point of the solvent binder is below 100°C.
6. The electrode plate according to claim 5, characterized in that: The solvent binder includes one of cyclohexane, cyclopentane, n-pentane, ethane, isooctane, trimethylpentane, diethyl ether, propyl ether, petroleum ether and benzene.
7. A method for preparing an electrode sheet, characterized in that: The method for preparing the electrode sheet according to any one of claims 1 to 6 comprises the following steps: (1) mixing a first active material, a first conductive agent, and a first solid electrolyte uniformly, then adding a first binder and a first solvent binder, and then mixing uniformly and stirring at a high speed to fiberize the first solvent binder to obtain a first powder; (2) after the second active material, the second conductive agent and the second solid electrolyte are mixed evenly, a second binder and a second solvent binder are added, and after the mixture is evenly mixed, the mixture is stirred at a high speed to fiberize the second solvent binder to obtain a second powder; (3) respectively rolling the first powder and the second powder at room temperature to obtain a first electrode material layer and a second electrode material layer; (4) After rolling the first electrode material layer onto the current collector at room temperature, rolling the second electrode material layer onto the first material layer at 100-160° C. to obtain an electrode sheet.
8. The method according to claim 7, characterized in that The thickness of the electrode plate is 40-70 μm.
9. An all-solid-state battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet are the electrode sheets according to any one of claims 1 to 6 or the electrode sheets prepared by the method according to claim 7 or 8.
10. An electrical device, characterized in that: Including the all-solid-state battery as described in claim 9.
Citation Information
Patent Citations
Electrode plate as well as preparation method and application thereof
CN116525760A
Dry-method positive pole piece, lithium ion battery and preparation method of dry-method positive pole piece
CN116581249A
Double-layer coated positive electrode, preparation method thereof and all-solid-state battery
CN116779766A
Multi-layer all-solid-state battery and preparation method and application thereof
CN117996218A
Electrode, battery, and method for manufacturing electrode
US20220085381A1